E-COMMERCE KERAJINAN TANGAN DESA BULUH KASAB: E-COMMERCE, HANDICRAFT, BULUH KASAB VILLAGE. - Tamrinsyah; Purnama, Fery; Musa Hendra, Dipu (FORTECH (Journal of Information Technology), 2019)
Buluh Kasab Village is one of the villages in Sungai Rengas Village, Kec. Maro Sebo Ulu, Kab. Batang Hari, Jambi. This village produces handicrafts in the form of caping hats, screwpine leaves mats, beaded bags, etc. Made by Youth Organization members, Buluh Kasab Village. In this case Buluh Kasab Village is used as a research location because so far the sales system, data collection, and sales reports are still using the old system by using the agenda book as a tool to collect goods and produce sales reports, a relatively narrow on market share. making the process of selling craft products less smooth. The purpose of this study is to build an E-Commerce system to facilitate  Youth Organization to process goods data, expand market share to produce reports on sales of handicraft products. Input in this system is in the form of customer data, item data, shipping data, transaction data and item category data. In this system there is a process of entering data, processing transaction data, making reports on stock data, reports on sales results. Output of the E-Commerce system are sales reports, transaction data reports and stock data data reports. E-Commerce system is expected to be able to help  Youth Organization in Buluh Kasab Village in improving the sales process and data collection in a more detailed and detailed way and can expand market share.